P'engaruh penambahan metionin dan sodium sulfat terhadap pertumbuhan dan konsentrasi asam amino bebas dalam serum darah ayam umur 3 minggu - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1993)
A study on the effect of adding methionine and sodium sulfate in diets on the growth and free amino acids concentration in blood serum of broiler chicks was carried out. This study was followed a randomized complete design with four diets as treatments. Twenty five chicks were used for each treatment and they were reared up to 3 weeks of age. The results showed that the chicks fed diet 2 (control + 0,44% methionine) were heavier than the chicks fed diet 1 (control) and diet 3 (control + 0,60% Na2SO4). There was no significant different on body weights between chicks fed diet 2 and diet 4 (control + 0,44% methionine + 0,60% Na2SO4). Furthermore, the chicks fed diet 2 and diet 4 had better feed conversion ratio than the chicks fed diet 1 and 3. Adding methionine in the diets increased concentration of glutamine, alanine, cysteine, methionine, thyroxine, phenylalanine, arginine, hydraxy praline, and asparagine in blood serum of broiler chicks at 3 weeks of age. But, there was no effect of adding Na2SO4 in the diets on the concentration of those amino acids. It is suggested not to add Na2SO4 on the diets which lack of methionine.